Features and Problematic Issues of The Tourism Development in Ukraine Due to The Coronavirus Covid-19 Pandemic - Liudmyla NIEMETS; Serhii KOSTRIKOV; Yurii KANDYBA; Nataliya DOBROVOLSKAYA; Pavlo KOBYLIN; Hanna KUCHERIAVA (Communications of International Proceedings, 2020)
The paper  focuses on those features of the tourism development in Ukraine, that became dominant ones over the last decade.  The problematic issues that the  this industry faces in the context of the coronavirus COVID-19 pandemic have been identified, and the ways of their resolving have been proposed. It has been  outlined that  the domestic tourism  is expected to be  developed in Ukraine in the post-quarantine period mainly in its structure excursion. educational, health resort, and in active   tourism domains.
Keywords: tourism in Ukraine; tourism domains; domestic tourism; foreign tourism; tourist flows; coronavirus COVID-19